Altered Landscapes and Filmic Environments: An Account from the 13th Asian Cinema Studies Society Conference. Issue 1 (1st June 2019) - Quiling Jr., Tito R.
Abstract : It's just past 10:00 am on a humid Monday in Singapore, and the streets seemed to have settled after a workday rush. My walk from Arab Street to McNally Street was rather placid, punctuated by moments at intersections, and surrounded by people heading somewhere. Minutes later, I was looking up at the postmodern buildings of LASALLE College of the Arts—a panorama of reinforced concrete, glass, tiles, and steel gleaming under the morning sun. In cinema, spaces and landscapes are primary features. At times, the setting goes beyond the overarching narrative, as it conveys its own story. Given their impact, Stephen Heath (2016) infers that a process occurs in identifying spatial connections to the characters, since "organizing, guiding, sustaining and reestablishing the space are the factors that reveal this process." The audience absorbs the familiar images or experiences onscreen. However, embodied objects of varying iterations contribute to how environments in films are concretized. On this note, one can ask: in what ways do filmic environments thus project narratives and discourses?